Laser pretreatment method for improving film-substrate binding force of PVD (Physical Vapor Deposition) coating on surface of magnesium alloy

Through laser pretreatment technology, the functional micro-nanostructure is created on the surface of magnesium alloy, which solves the problem of unsatisfactory film-based binding force of the PVD coating on the surface of magnesium alloy, and realizes high-precision and high-efficiency magnesium alloy surface treatment, significantly improving the coating The bonding force avoids surface oxidation inclusions.

CN119307856APending Publication Date: 2025-01-14CHENGDU IND VOCATIONAL TECHN COLLEGE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411423742.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The binding force of the PVD coating film base of the existing magnesium alloy surface is not ideal, the treatment accuracy is not high, the treatment range is uncontrollable, and the surface is prone to oxidation.

Method used

The surface of the magnesium alloy matrix is ​​polished, polished, and ultrasonic cleaned by laser pretreatment. Then, under the protection of inert gas, high-precision laser is used to create a functional micro-nano structure, adjust the wettability of the substrate and improve the coating bonding force.

Benefits of technology

The PVD coating film-based bonding force on the surface of magnesium alloy is improved, with high processing accuracy, high efficiency and controllable range, avoiding surface oxidation inclusions, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307856A_ABST
    Figure CN119307856A_ABST
Patent Text Reader

Abstract

The invention provides a laser pretreatment method for improving film-substrate binding force of a PVD (Physical Vapor Deposition) coating on a magnesium alloy surface, and belongs to the technical field of magnesium alloy surface treatment. According to the method, a functional micro-nano structure is processed on the surface of the magnesium alloy base material through ultrafast laser treatment under the protection of inert gas, so that the wettability of the base material is changed, and the film-substrate binding force of the PVD coating on the surface of the magnesium alloy is effectively improved. The pretreatment method provided by the invention is high in machining precision, high in machining efficiency and accurate and controllable in machining range, can effectively avoid surface oxide inclusion, and has a good application prospect. The pretreatment method also provides a method for realizing controllable film-substrate binding force gradient of the PVD coating on the surface of the magnesium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloy surface treatment, and in particular to a laser pretreatment method for improving the bonding strength of a PVD coating film-base on the surface of a magnesium alloy. Background Art

[0002] Preparing metal and its nitride coating on the surface of magnesium alloy by physical vapor deposition (PVD) coating technology is an important method to improve the surface properties of magnesium alloy. However, due to the differences in properties such as crystal structure, material hardness, and linear expansion coefficient between magnesium alloy and coating material, the film-based bonding between the magnesium alloy substrate and the PVD coating on its surface is often not ideal. In order to improve the film-based bonding between magnesium alloy and the PVD coating on its surface, pretreatment processes such as sandblasting, thermal spraying, and micro-arc oxidation are generally used before PVD coating. However, the current pretreatment methods still have many problems such as low processing accuracy, uncontrollable processing range, and easy surface oxidation. Summary of the invention

[0003] The purpose of the present invention is to provide a laser pretreatment method for improving the bonding strength of PVD coating film on the surface of magnesium alloy, so as to solve the technical problems of low processing precision, uncontrollable processing range and easy surface oxidation in the prior art.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a laser pretreatment method for improving the film-base bonding strength of a PVD coating on a magnesium alloy surface, comprising the following steps:

[0006] (1) grinding and polishing the surface of the magnesium alloy substrate, and then ultrasonically cleaning it to obtain a pretreated magnesium alloy substrate;

[0007] (2) Under the protection of inert gas, the surface of the magnesium alloy substrate is pretreated by laser to obtain a magnesium alloy substrate with functional micro-nano structures on the surface;

[0008] The output power of the laser is 100-2000mw, and the pulse repetition frequency of the laser is 100-300kHz.

[0009] Furthermore, the pulse width of the laser is ≤10ps, and the focused spot diameter is ≤40μm.

[0010] Furthermore, the scanning speed of the laser is 10 to 1000 mm / s, and the scanning interval is 1 to 20 μm.

[0011] Furthermore, the scanning path of the laser is a straight line or a cross-net structure, and the scanning is repeated 1 to 5 times.

[0012] Furthermore, the inert gas comprises high-purity argon gas, the purity of the high-purity argon gas is ≥99.999%, the pressure of the inert gas is 0.2-0.6 MPa, and the flow rate of the inert gas is 10-20 L / min.

[0013] Furthermore, the cleaning is carried out by ethanol ultrasonic cleaning, and the cleaning time is 30 minutes.

[0014] Beneficial effects of the present invention:

[0015] The present invention provides a laser pretreatment method for improving the film-substrate bonding strength of PVD coating on the surface of magnesium alloy. The method has high processing accuracy, high processing efficiency, and a precisely controllable processing range. Surface oxidation inclusions can be effectively avoided during the processing. Functional micro-nano structures are processed on the surface of the magnesium alloy substrate to change the wettability of the substrate, thereby effectively improving the film-substrate bonding strength of the PVD coating on the surface of the magnesium alloy. The method has good application prospects.

[0016] The pretreatment method of the present invention also provides a method for achieving controllable gradient of film-base bonding force of PVD coating on the surface of magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the laser preprocessing method of the present invention. DETAILED DESCRIPTION

[0018] The present invention provides a laser pretreatment method for improving the film-base bonding strength of a PVD coating on a magnesium alloy surface, comprising the following steps:

[0019] (1) grinding and polishing the surface of the magnesium alloy substrate, and then ultrasonically cleaning it to obtain a pretreated magnesium alloy substrate;

[0020] (2) Under the protection of inert gas, the surface of the magnesium alloy substrate is pretreated by laser to obtain a magnesium alloy substrate with functional micro-nano structures on the surface;

[0021] The output power of the laser is 100-2000mw, and the pulse repetition frequency of the laser is 100-300kHz.

[0022] In the present invention, the output power of the laser is 100-2000 mw, preferably 200-1800 mw, and more preferably 500-1500 mw; the pulse repetition frequency of the laser is 100-300 kHz, preferably 150-250 kHz, and more preferably 180-220 kHz.

[0023] In the present invention, the pulse width of the laser is ≤10 ps, ​​preferably ≤9 ps, and more preferably ≤8 ps; the focused spot diameter is ≤40 μm, preferably ≤35 μm, and more preferably ≤30 μm.

[0024] In the present invention, the scanning speed of the laser is 10 to 1000 mm / s, preferably 50 to 900 mm / s, more preferably 200 to 800 mm / s, and more preferably 300 to 500 mm / s; the scanning interval is 1 to 20 μm, preferably 5 to 15 μm, and more preferably 8 to 10 μm.

[0025] In the present invention, the scanning path of the laser is a straight line or a cross-net structure, preferably a straight line structure; the scanning repetition number is 1 to 5 times, preferably 2 to 3 times.

[0026] In the present invention, the inert gas comprises high-purity argon gas, and the high-purity argon gas is used to protect the laser spot ablation during the laser treatment process; the purity of the high-purity argon gas is ≥99.999%, and the pressure of the inert gas is 0.2-0.6MPa, preferably 0.3-0.5MPa, and more preferably 0.4MPa; the flow rate of the inert gas is 10-20L / min, preferably 12-18L / min, and more preferably 15L / min.

[0027] In the present invention, the cleaning adopts ethanol ultrasonic cleaning, and the cleaning time is 30 minutes.

[0028] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0029] Example 1

[0030] After grinding, polishing and cleaning the surface of the magnesium alloy substrate, the surface of the magnesium alloy substrate was laser pretreated using an ultrafast laser processing system with a wavelength of 1064nm, a pulse width of 8ps, and a focused spot diameter of 40μm. The laser spot ablation area was protected by high-purity Ar2, the gas pressure was set to 0.2MPa, and the flow rate was set to 10L / min. The specific process parameters are shown in Laser Process 1 in Table 1.

[0031] The magnesium alloy after laser treatment was placed in alcohol for ultrasonic cleaning for 30 min. The PVD coating was carried out using a multi-arc ion plating equipment with dual targets. The cavity was preheated to 250 °C and the cavity was pre-evacuated to 4.0 × 10 -3 Pa, the specific PVD process parameters are shown in Table 2 for coating Cr.

[0032] According to the micron scratch test results, the critical pressure L of the coating Cr after laser process 1 treatment c2 is 38.8N, which is lower than the critical pressure L of the Cr coating on the substrate without laser treatment. c2 It is 28.1N. The laser treatment process increases the bonding strength of Cr coating on the surface of magnesium alloy.

[0033] Example 2

[0034] After grinding, polishing and cleaning the surface of the magnesium alloy substrate, the surface of the magnesium alloy substrate was laser pretreated using an ultrafast laser processing system with a wavelength of 1064nm, a pulse width of 8ps, and a focused spot diameter of 40μm. The laser spot ablation area was protected by high-purity Ar2, the gas pressure was set to 0.2MPa, and the flow rate was set to 10L / min. The specific process parameters are shown in Laser Process 2 in Table 1.

[0035] The magnesium alloy after laser treatment was placed in alcohol for ultrasonic cleaning for 30 min. The PVD coating was carried out using a multi-arc ion plating equipment with dual targets. The cavity was preheated to 250 °C and the cavity was pre-evacuated to 2.0 × 10 -3 Pa, the specific PVD process parameters are shown in Table 2 for coating Cr.

[0036] According to the micron scratch test results, the critical pressure L of the coating Cr after laser process 2 treatment c2 is 43.8N, which is lower than the critical pressure L of the Cr coating on the substrate without laser treatment. c2 It is 28.1N. The laser treatment process increases the bonding strength of Cr coating on the surface of magnesium alloy.

[0037] Example 3

[0038] After grinding, polishing and cleaning the surface of the magnesium alloy substrate, the surface of the magnesium alloy substrate was laser pretreated using an ultrafast laser processing system with a wavelength of 1064nm, a pulse width of 8ps, and a focused spot diameter of 40μm. The laser spot ablation area was protected by high-purity Ar2, the gas pressure was set to 0.2MPa, and the flow rate was set to 10L / min. The specific process parameters are shown in Laser Process 3 in Table 1.

[0039] The magnesium alloy after laser treatment was placed in alcohol for ultrasonic cleaning for 30 min. The PVD coating was carried out using a multi-arc ion plating equipment with dual targets. The cavity was preheated to 250 °C and the cavity was pre-evacuated to 4.0 × 10 -3 Pa, the specific PVD process parameters are shown in Table 2 for coating Cr.

[0040] According to the micron scratch test results, the critical pressure L of the coating Cr after laser process 3 treatment c2 is 37.1N, compared with the critical pressure L of the Cr coating on the substrate without laser treatment. c2 It is 17.9N. The laser treatment process increases the bonding strength of Cr coating on the surface of magnesium alloy.

[0041] Example 4

[0042] After grinding, polishing and cleaning the surface of the magnesium alloy substrate, the surface of the magnesium alloy substrate was laser pretreated using an ultrafast laser processing system with a wavelength of 1064nm, a pulse width of 8ps, and a focused spot diameter of 40μm. The laser spot ablation was protected by high-purity Ar2, the gas pressure was set to 0.4MPa, and the flow rate was set to 15L / min. The specific process parameters are shown in Laser Process 2 in Table 1.

[0043] The magnesium alloy after laser treatment was placed in alcohol for ultrasonic cleaning for 30 min. The PVD coating was carried out using a multi-arc ion plating equipment with dual targets. The cavity was preheated to 250 °C and the cavity was pre-evacuated to 4.0 × 10 -3 Pa, the specific PVD process parameters are shown in Table 2 for coating Cr.

[0044] According to the micron scratch test results, the critical pressure L of the CrN coating after laser process 2 treatment c2 is 19.1N, compared with the critical pressure L of CrN coating on substrate surface without laser treatment. c2 It is 12.3N. The laser treatment process increases the bonding strength of the CrN coating on the magnesium alloy surface.

[0045] Example 5

[0046] After grinding, polishing and cleaning the surface of the magnesium alloy substrate, the surface of the magnesium alloy substrate was laser pretreated using an ultrafast laser processing system with a wavelength of 1064nm, a pulse width of 8ps, and a focused spot diameter of 40μm. The laser spot ablation area was protected by high-purity Ar2, the gas pressure was set to 0.2MPa, and the flow rate was set to 20L / min. The specific process parameters are shown in Laser Process 2 in Table 1.

[0047] The magnesium alloy after laser treatment was placed in alcohol for ultrasonic cleaning for 30 min. The PVD coating was carried out using a multi-arc ion plating equipment with dual targets. The cavity was preheated to 250 °C and the cavity was pre-evacuated to 4.0 × 10 -3 Pa, the specific PVD process parameters are shown in Table 2 for coating TiN.

[0048] According to the micron scratch test results, the critical pressure L of the TiN coating after laser process 2 treatment c2 is 31.9N, compared with the critical pressure L of TiN coating on the substrate without laser treatment. c2 It is 20.5N. The laser treatment process increases the bonding strength of the TiN coating on the magnesium alloy surface.

[0049] Example 6

[0050] After grinding, polishing and cleaning the surface of the magnesium alloy substrate, laser pretreatment was performed using an ultrafast laser processing system with a wavelength of 1064nm, a pulse width of 8ps, and a focused spot diameter of 40μm. The laser spot ablation was protected by high-purity Ar2, the gas pressure was set to 0.6MPa, and the flow rate was set to 10L / min. The specific process parameters are shown in Laser Process 2 in Table 1.

[0051] The magnesium alloy after laser treatment was placed in alcohol for ultrasonic cleaning for 30 min. The PVD coating was carried out using a multi-arc ion plating equipment with dual targets. The cavity was preheated to 250 °C and the cavity was pre-evacuated to 4.0 × 10 -3 Pa, the specific PVD process parameters are shown in Table 2 for coating AlTiN.

[0052] According to the micron scratch test results, the critical pressure L of the AlTiN coating after laser process 2 treatment c2 33.6N, compared with the critical pressure L of AlTiN coating on the substrate without laser treatment c2 It is 26.7N. The laser treatment process increases the bonding strength of the AlTiN coating on the magnesium alloy surface.

[0053] Table 1 Ultrafast laser pretreatment process parameters

[0054]

[0055] Table 2 PVD coating process parameters

[0056]

[0057]

[0058] It can be seen from the above embodiments that the present invention provides a laser pretreatment method for improving the film-substrate bonding strength of PVD coating on the surface of magnesium alloy. The method has high processing accuracy, high processing efficiency, and a precisely controllable processing range. Surface oxidation inclusions can be effectively avoided during the processing. Functional micro-nano structures are processed on the surface of the magnesium alloy substrate to change the wettability of the substrate, thereby effectively improving the film-substrate bonding strength of the PVD coating on the surface of the magnesium alloy. The method has good application prospects.

[0059] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A laser pretreatment method for improving the bonding strength of PVD coating film on magnesium alloy surface, characterized in that: The following steps are involved: (1) grinding and polishing the surface of the magnesium alloy substrate, and then ultrasonically cleaning it to obtain a pretreated magnesium alloy substrate; (2) Under the protection of inert gas, the surface of the magnesium alloy substrate is pretreated by laser to obtain a magnesium alloy substrate with functional micro-nano structures on the surface; The output power of the laser is 100-2000mw, and the pulse repetition frequency of the laser is 100-300kHz.

2. The laser pretreatment method for improving the film-base bonding strength of PVD coating on the surface of magnesium alloy according to claim 1, characterized in that: The pulse width of the laser is ≤10ps, and the focused spot diameter is ≤40μm.

3. The laser pretreatment method for improving the film-base bonding strength of PVD coating on the surface of magnesium alloy according to claim 1 or 2, characterized in that: The scanning speed of the laser is 10-1000 mm / s, and the scanning interval is 1-20 μm.

4. The laser pretreatment method for improving the film-base bonding strength of PVD coating on the surface of magnesium alloy according to claim 3, characterized in that: The scanning path of the laser is a straight line or a cross-net structure, and the scanning is repeated 1 to 5 times.

5. The laser pretreatment method for improving the film-base bonding strength of PVD coating on the surface of magnesium alloy according to claim 1 or 4, characterized in that: The inert gas comprises high-purity argon gas, the purity of the high-purity argon gas is ≥99.999%, the pressure of the inert gas is 0.2-0.6 MPa, and the flow rate of the inert gas is 10-20 L / min.

6. The laser pretreatment method for improving the film-base bonding strength of PVD coating on the surface of magnesium alloy according to claim 1, characterized in that: The cleaning is carried out by ultrasonic cleaning with ethanol, and the cleaning time is 30 minutes.

Citation Information

Patent Citations

  • Laser method for improving binding force of ceramic coating and metal matrix

    CN109112602A

  • Method for preparing micro-nano periodic structure on surface of amorphous alloy through nanosecond laser irradiation

    CN113070576A

  • Preparation method of fuel cell metal pole plate coating

    CN113206267A